Does A Student’s Interest in Writing and Vocabulary Mastery Have An Impact on Their Writing Ability in Tenth Grade at SMK Negeri 2 Muara Enim? - Ramayanti, Ike; Tahrun, Tahrun; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2023)
Writing This article aims to look at: first, the effect that occurs between writing interest variables on writing ability, second, the effect that occurs between mastery vocabulary variables on writing ability, and lastly the interactions that occur between the variables in the study. In analyzing the data, we employed a using the triangulation approach with descriptive analysis. From the results of the analysis, researchers have found: that writing interest has an impact on writing ability, and that vocabulary mastery has an impact on writing ability. Additionally, writing interest and vocabulary mastery have a large impact on writing ability.